2020
DOI: 10.1016/j.ajp.2020.102451
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of e-consult for Substance Use Disorders during the COVID 19 pandemic: A study from India

Abstract: Highlights Digital health tool has been employed to increase access to care for the patient with SUD during COVID 19 pandemic. E-consult, a mobile-friendly tool, connects remote health care providers (HCPs) with addiction specialists. Consultation for the cases, as well as educative materials, was offered to the HCPs. This asynchronous telepsychiatry may be more suited for a busy specialist from a developing country like India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 25 publications
0
30
0
5
Order By: Relevance
“…Finally, changes in treatment provision were documented. Studies reported reduced treatment provision early in the pandemic, but as the pandemic progressed [52] , [53] , [54] , providers were incorporating telemedicine and other techniques [55] , [56] .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, changes in treatment provision were documented. Studies reported reduced treatment provision early in the pandemic, but as the pandemic progressed [52] , [53] , [54] , providers were incorporating telemedicine and other techniques [55] , [56] .…”
Section: Resultsmentioning
confidence: 99%
“…Another important way to reduce the treatment gap is to harness technology [ 57 ]. One such example is e-consult for people with SUD during the pandemic and training support to healthcare workers in distant places to manage with SUD [ 118 ]. Telehealth, group meetings and online consultations can be some ways to handle the increased demand during and after pandemic [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…O programa CopeColumbia, formado por 186 grupos de profissionais de saúde em um hospital, com foco no suporte emocional frente às dificuldades emergentes do contexto da pandemia, estratégias de coping e resiliência, controle do estresse e ansiedade, traumas, perdas e lutos, foi considerado um espaço seguro para o tratamento de saúde mental 32 ; assim como o programa e-consult para usuários de SPA's na Índia, pois a maioria dos profissionais revelou boa aceitação (98%) frente à intervenção psicológica realizada 24 , o que denota a evidência positiva de acessibilidade e cuidado desse tipo de atendimento. As 6.800 intervenções realizadas por meio de chamadas de vídeo e serviços de mensagens eletrônicas na República Dominicana evidenciaram o sofrimento psicológico da população na pandemia, em meio à ansiedade (43%), depressão (15%), problemas de sono (26%) e comportamentos relacionados ao suicídio (2%) 22 .…”
Section: Discussionunclassified
“…O potencial do uso da linha telefônica mostrou impacto para além da redução de problemas psicológicos, como ansiedade, depressão e transtorno de pânico [13][14][15][16][17] , e no tratamento de pacientes com psicoses 18,19 , tendo em vista o medo de contágio com o vírus. O uso da telessaúde [20][21][22][23][24][25][26] e da psicoterapia on-line ou por telefone 14 para os profissionais de saúde no enfrentamento da pandemia foi positivo, e com menor número de desistência quando comparada ao atendimento presencial 27,28 .…”
Section: Fonte: Secchi Et Al (2021)unclassified
See 1 more Smart Citation